Production of carbon via Electrochemical conversion of CO2 in carbonate based Molten Salt - Miron Gakim; lam Mun Khong; Jidon Janaun; Wiley Liew Yun Hsein; Nancy Julius Siambun (Trans Tech Publications, Switzerland., 2015)
Carbon was successfully deposited on AISI 304 stainless steel rod cathode through electrolysis process in three molten salt mixtures, namely K2CO3-Li2CO3 (mole ratio: 1:1), CaCO3-Li2CO3-LiCl (mole ratio 0.09:0.28:0.63) and CaCO3-CaCl2-KCl-LiCl (mole ratio: 0.13:0.31:0.10:0.45), under CO2 atmospheres as continuous source of carbon. The process were carried out for 1 hour at temperature range 545–585°C and electrolysis voltage of 4.0V to drive the deposition of carbon through electrochemical conversion. EDX analysis on deposited products shown carbon as dominant element (89-98%). SEM revealed carbon with Flakes and grapes aggregation shapes for different salt mixtures. The achieved current efficiency of 83.8%, 80.46% and 92.41% were found in the respective salt mixtures, and energy consumption promotes several ways for efficiency improvement on the electrochemical conversion of CO2.